Evaluasi Kepuasan Kerja Karyawan di Industri Manufaktur Presisi melalui Pendekatan Importance-Performance Analysis - Khairullah, Mohammad Reatha Deo; Tarigan , Amenda Septiala; Alamsyah, Nanang; Kurnia, Tyas Eka (Jurnal Serambi Engineering, 2026)
The precision manufacturing sector requires a stable and competent workforce to ensure smooth production processes, making an understanding of employee job satisfaction essential for maintaining organizational performance. This study aims to evaluate employee satisfaction at PT XYZ using a descriptive quantitative approach through a survey of 21 purposively selected respondents. Data were collected using a closed-ended questionnaire consisting of ten job satisfaction indicators and analyzed using the Importance-Performance Analysis (IPA) framework. The results show an employee satisfaction index of 74.35 percent, indicating a moderately satisfied category. The IPA mapping reveals that interpersonal relation requires priority improvement due to its high importance but relatively low satisfaction level. Meanwhile, quality of work, knowledge of job, dependability, and performance fall into the category of attributes that should be maintained. Other indicators such as adaptability, initiative and resourcefulness, judgment, and leadership quality show both low importance and low satisfaction, suggesting that gradual attention is still needed to strengthen the company’s long-term organizational performance.